The Functions of the Board of Directors in Corporate Philanthropy: An Empirical Study From China - Pan, Qi; Huang, Zhangjie (Frontiers in Psychology, 2022)
As an important way for enterprises to fulfill social responsibility, corporate philanthropy (CP) has attracted much attention from the academic community. But there are still few well-targeted theoretical and empirical studies on what functions the board of directors (BOD) should perform to better fulfill philanthropic responsibilities. Taking this deficiency as a breakthrough, this study focuses on Chinese state-owned and private enterprises to analyze and test the functions performed by the BOD in CP. Based on the sample of Chinese A-share listed companies from 2008 to 2019, the empirical results show that the BOD of state-owned enterprises mainly performs a monitoring function in CP while that of private enterprises mainly performs a consulting function. The above findings remain valid when potential biases in the quantitative analysis are considered. Further research shows that environmental dynamism and board fault lines inhibit the performance of the above two functions. The contributions of the study include clarifying the functional characteristics of the BOD in CP and its influencing factors, revealing new theories to the formation mechanism of CP, which provide references for enterprises to optimize philanthropic decision-making. The limitation should also be emphasized that our findings are based only on Chinese contexts.